2010
DOI: 10.1017/s0954394510000177
|View full text |Cite
|
Sign up to set email alerts
|

The sociolinguistic variant as a carrier of social meaning

Abstract: Traditionally used as a "heuristic device" (Labov, 1978), the sociolinguistic variable has taken on a new role as a primitive of speaker/hearer mental models in third-wave variation work (Eckert, 2005(Eckert, , 2008. Results from a sociolinguistic perception study suggest that at least in some cases, variants of the same variable function independently as loci of indexically linked social meaning. Listener responses were collected to three matched guises of the English variable (ING): -in, -ing, and a neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 38 publications
7
79
1
1
Order By: Relevance
“…The unfairness inherent in accent-based discrimination may well be unpalatable to many career practitioners, and this may have an impact on their worldview. An alternative explanation could lie in the fact that this cognitive processing takes place below the level of consciousness (Campbell-Kibler, 2010;Chartrand & Bargh, 1999). Practitioners may therefore not be aware of the extensive impact that accent has within society, nor indeed be fully cognisant of their own responses to accent.…”
Section: Discussionmentioning
confidence: 99%
“…The unfairness inherent in accent-based discrimination may well be unpalatable to many career practitioners, and this may have an impact on their worldview. An alternative explanation could lie in the fact that this cognitive processing takes place below the level of consciousness (Campbell-Kibler, 2010;Chartrand & Bargh, 1999). Practitioners may therefore not be aware of the extensive impact that accent has within society, nor indeed be fully cognisant of their own responses to accent.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on these findings, it is likely that results for the US and (different areas within) Britain may differ-certainly on the professionalism scale, but (ing) is associated with a variety of different attributes. Campbell-Kibler (2007, 2011 in research on the perceived social meanings of the variants of (ing) in the US found that [ɪŋ]-guises were rated as significantly more educated, intelligent, articulate-sounding and less likely to be a student, while [ɪn]-guises were rated as sounding significantly more informal and less likely to be gay-sounding. In her (2009) We are interested in these meaning constellations, but we also wish to explore an additional layer of meaning in this study: one based on respondent background.…”
Section: Social Evaluationmentioning
confidence: 99%
“…Language is one oftused resource for showing membership in certain demographic categories through the use of enregistered linguistic variables such as (ING)/(IN) variation, shifted vowels, or lexical choices (Agha 2006;Campbell-Kibler 2011). Some language features that index identity features cannot be changed or hidden easily if they are connected to an identity that a speaker does not want to reveal -for example, the pitch of one's voice and the amount of politeness are indicators of gender (Herring and Matinson 2004) and different sets of pronunciations index a speaker's location, ethnicity, or native language.…”
Section: Methodsmentioning
confidence: 99%